Genetics and livestock breeding in the UK: Co-constructing technologies and heterogeneous biosocial collectivities - Morris, Carol; Holloway, Lewis (Elsevier, 2014)
Cattle and sheep breeders in the UK and elsewhere are increasingly being encouraged to use a variety of genetic technologies to help them make breeding decisions. The technology of particular interest here is ‘classical’ statistical genetics, which use a series of measurements taken from animals’ bodies to provide an estimate of their ‘genetic merit’ known as Estimated Breeding Values (EBVs). Drawing on empirical research with the representatives of national cattle breed societies and individual cattle breeders the paper explores the complex ways in which they are engaging with genetic breeding technologies. The concept of ‘heterogeneous biosocial collectivity’ is mobilised to inform an understanding of processes of co-construction of breeding technologies, livestock animals and humans. The paper presents case studies of livestock breeding collectivities at different scales, arguing that the ways in which the ‘life’ of livestock animals is problematised is specific to different scales, and varies too between different collectivities at the same scale. This conceptualisation problematises earlier models of innovation-adoption that view farmers as either ‘adopters’ or ‘non-adopters’ of technologies and in which individual attitudes alone are seen as determining the decision to adopt or not adopt. Instead, the paper emphasises the particularity and specificity of co-construction, and that the co-construction of collectivities and technologies is always in process.